PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK ASSERTIVE TRAINING TERHADAP INTERAKSI SOSIAL SISWA SMK NUR AZIZI TANJUNG MORAWA T.A 2024/2025 - Namira Salsabila Rahmadani; Nur Asyah; Nurul azmi Saragih; Dina Hidayati Hutasuhut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of group guidance services with assertive trainingtechniques on social interactions of SMK Nur Azizi Tanjung Morawa students in the2024/2025 Academic Year. Group guidance services with an assertive training approachplay an important role in improving students' ability to interact socially in a healthy andpositive way in their social environment and in their surroundings. Through the applicationof this assertive training technique, students are expected to be able to overcome various obstacles in communicating and interacting with others such as shyness, lack of self-confidence, or fear of rejection. This study uses a quantitative approach with a pre-experimental one group pretest-posttest design with the help of the SPSS version 23.00 for windows program. The population in this study was 72 students, and samples were takenby purposive sampling of 10 students who had low levels of social interaction. The resultsof data analysis in this study showed a significance value (2-tailed) of 0.00 and a t-test valueof 7.370, which indicates that group guidance services with assertive training techniqueshave a significant effect on improving students' social interactions at school. Thus, it can beconcluded that this intervention is effective in helping students develop better social skills.This finding is expected to be a reference for BK teachers in designing appropriate guidanceservices to improve students' social interactions at school.